2018
DOI: 10.21660/2018.50.95424
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polyethersulfone Membranes Using Nanocarbon as Additive

Abstract: Membrane-based processes have become the most dominant technology for water or wastewater treatment. To maintain optimum performance, a membrane should have high permeability and selectivity, good hydrophilicity, in combination with stable mechanical properties. Generally, the membrane produced from pure polyethersulfone (PES) has good mechanical properties, but low hydrophilicity. Modifications of the PES membrane with hydrophilic additives can increase its hydrophilicity. Nevertheless, incorporating additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…A high-performance membrane is often produced by embedding a filler that has a nanoscale [2]. This helps to enhance its functional properties in separating and purifying water [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A high-performance membrane is often produced by embedding a filler that has a nanoscale [2]. This helps to enhance its functional properties in separating and purifying water [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The number of methods available for removal of As(III) from water and waste water solutions which include reverse osmosis, chemical coagulation, chemical precipitation, electrochemical methods, membrane filtration, ion exchange process (Arahman et al 2018, Khan, Sherazi et al 2018, Sherazi et al 2022). Among all the above described techniques, adsorption is more efficient and ideal technique for removal of As(III) from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with this problem, pursuit on the effective methods to reduce and control membrane fouling have been done through various endeavors [ 8 , 11 , 12 , 13 ]. Though the mechanism and behavior of fouling are complex, it has been widely reported that increasing the hydrophilicity of the membrane can be one of the viable solutions to limit the rate of foulant adsorption and thereby reducing the membrane fouling severity [ 14 , 15 , 16 , 17 , 18 , 19 ]. The enhancement of the hydrophilicity can be done by introducing a hydrophilic additive into the membrane materials through various techniques, such as blending [ 20 , 21 , 22 , 23 , 24 ], coating [ 25 , 26 ], grafting [ 27 ] and so forth.…”
Section: Introductionmentioning
confidence: 99%